PENGARUH PENGGUNAAN MEDIA SOSIAL INSTAGRAM TERHADAP PERILAKU BERAGAMA SISWA DAN SISWI MADRASAH ALIYAH NEGERI (MAN) 1 KOTA PADANG PANJANG - Febriani Mariyah; Yusuf Afandi (KOLONI, 2022)
This research is to find how much influence the use of social media Instagram has on the religious behavior of students at Madrasah Aliyah Negeri (MAN) 1 Padang Panjang city. This research uses the Taro Yamane formula. The population in this study was 214 students and the sample was 69 students. The method used is to use quantitative research whit the type of field research. Sampling technique is propotional random sampling. The questionnaire that the researchers distributed was by using a Likert Scale. Analisys prerequisite test, namely normality test and linearity test. Hypothesis testing is done by comparing the Fcalculated whit the Ftable whit a precision level of 10%. The result of research conducted using the SPSS version 16.0 program show the Fcalculated is (158,754) with Ftable of (2,78), based on the above calculations it can be concluded that Ha is accepted and HO is rejected, it can be interpreted that there is a significant influence between the variables of use Instagram social media on the religious behavior of students at the Madrasah Aliyah Negeri (MAN) 1 Padang Panjang City. Keywords: use of social media Instagram, religious bahavior